Effect of Lipopolysaccharide Extracted from Pseudomonas aeruginosa Bacterium on the Number of Immune Cells and Some Cytokines in White Rats - Mohammed, Dhuha Jasem; AL-Tareea, Rana Khalid Ahmed; Hamed, Nawar Talal (Iraqi Journal of Science, 2026)
Lipopolysaccharide (LPS) has a role in activating the immune system, including immune cells and interleukins. The current study aimed to estimate the levels of immune factors compared with control. LPS was extracted from Pseudomonas aeruginosa by a modified EDTA method. Three concentrations, 625, 1250, and 2500 µg/100gm of weight were prepared. Rats injected with a calculated dose, followed by a booster dose for two weeks. The results showed a significant increase in the number of neutrophils (3.009±0.002, 2.054±0.001, and 2.719±0.010) ×103 µL, and the number of lymphocytes (5.954 ± 0.003, 4.902 ± 0.02, and 5.423 ± 0.1) ×103 µL at the concentrations of 625, 1250, and 2500µ g/100gm, compared to control (2.775±0.100) and (4.207 ± 0.007) ×103 µL, all respectively. In addition, the results also revealed a considerable increase in the number of monocytes (0.319 ± 0.001, 0.362 ± 0.002, and 0.329 ± 0.002) ×103 µL for concentrations respectively compared to control (0.080±0.0003) ×103 µL. Moreover, the levels of interleukin-8 and interleukin-12 were measured in the serum samples; the outcomes displayed a remarkable difference in the level of (IL-8) as (354.00 ± 0.04) pg/ml at a concentration of 2500 mg/100gm compared to control (313.330 ± 0.04) pg/ml. Furthermore, the levels of (IL-12) revealed a significant rise (11.766 ± 1.738, 34.600 ± 3.05, 12.400 ± 0.556) pg/ml at all used concentrations, respectively, compared to control (6.600 ± 0.360) pg/ml. The current study concluded that lipopolysaccharides at different concentrations affected the total number of white cells and increased the number of lymphocytes, mononuclear cells, and the levels of immune cytokines compared to the control.